Recruitment and retention in longitudinal studies of people with intellectual disability: A case study of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA). (May 2022) - McCarron, Mary; McCausland, Darren; McGlinchey, Eimear; Bowman, Sarah; Foley, Michael; Haigh, Margaret; Burke, Eilish; McCallion, Philip
Highlights: Recruitment of people with intellectual disability requires clear vision and strategies. A multi-wave longitudinal study over a decade retained 87.1 % of surviving participants. Bespoke strategies aimed to removed barriers to participation for this population. Strategies to create a project community and study bond enhanced retention. A Values Framework and commitment to participant involvement were critical to success. Abstract: Background: Longitudinal study of people with intellectual disability and other difficult to reach populations requires specific recruitment and retention strategies to be successful. Aims: This paper provides a case study of participant recruitment and retention for a longitudinal study of ageing among older adults with intellectual disability in Ireland. Methods and procedures: Development and implementation of strategies to recruit and retain participants with intellectual disability aged 40+ years, for a longitudinal study comprising four data collection waves over more than a decade, are reported. Recruitment and retention outcomes are assessed alongside factors of successful implementation. Outcomes and results: A nationally representative sample of 753 individuals with intellectual disability was recruited for wave 1 of the study. Multiple retention strategies aimed to reduce barriers to participation and create a project community and study bond, underpinned by a Values Framework and commitment to PPI. After four waves over 11 years, 87.1 % of surviving participants were retained. Conclusions and implications: Successful recruitment and retention of people with intellectual disabilities in longitudinal studies is possible when the approach taken is personal, flexible, and innovative; participant burden is minimised; the research team is skilled and sensitive to needs of participants; and where involvement of the study population guides development and implementation of specific and bespoke strategies.